Scenarios planning: the evolution of prospective thinking - Pereira, Maurício Fernandes (2005)
The world is changing even more than before. Around the world, the organizational stability is in face of threats unnoticed before, due to technologic innovations, uncontrolled financial markets, up to date customers, and an observant society and government, in order to control the organizations’ social and environmental responsibilities. To face this threats, organizations needs to worry even more, renew its long range planning systems, and use Prospective Scenaries to find out, in a better way, the dynamic forces that will preveil in the next years. This paper seeks to clarify the source of prospective thinking that has created and developed this tool. Prospective Thinking is considered, nowadays, one of most innovatives tools used by the strategic management in organizations.